Investors’ trading intensity and Covid-19: evidence from the Malaysian stock market - Siew, Ken Wei (2022)
This research has successfully established and explained the key attributes that have a significant impact on investors’ trading behaviour during the Covid-19 pandemic. The focus of this study is mainly on Malaysian investors, with a sample period that covers from January 2020 to July 2021 and the logistic model was employed to describe our main findings on the factors affecting investors’ trading intensity. Our results determined that age, gender, investors’ risk tolerance and Covid-19 cases growth are positively significant to investors’ trading intensity. Stock market performance represented by the drop in KLCI Index also showed positive significance during the months of March 2020 and April 2020, showing that investors’ trading intensity is especially high during the movement control order period. This research is important to financial regulators in Malaysia who wish to understand the factors affecting investors’ trading behaviour for the purpose of designing new portfolios with investment allocations that caters to the needs and expectations of Malaysian investors as part of their corporate marketing strategy.